Glucocorticoid receptor involvement in goose (Anas cygnoides) pituitary somatotroph differentiation induced by glucocorticoids during embryonic development. Issue 4 (4th July 2019) - Yan, L.; Yu, J.; Chen, Z.; Chen, R.; Zhu, H.; Yan, J.; Shi, Z.
ABSTRACT: 1. In this study, geese ( Anas cygnoides ) embryonic pituitary cells were cultured in vitro to determine if glucocorticoids could induce growth hormone (GH) expression and to investigate the molecular mechanisms involved in this process. 2. On embryonic day 15 (e15) and e20 the pituitary cells were treated with corticosterone (CORT), membrane impermeable bovine serum albumin–conjugate corticosterone (CORT-BSA), dexamethasone (DEX), and a glucocorticoid receptor (GR) antagonist (RU486) to detect responsiveness of somatotrophs to glucocorticoids. 3. Treatment with CORT, CORT-BSA, and DEX for as little as 6 h increased the percentage of GH-positive cells ( P < 0.01) and increased GH mRNA expression (P < 0.01) in e15 goose pituitary cells compared to the control. CORT significantly increased the level of GH protein secreted from cultured e15 goose embryonic pituitary cells, and CORT-BSA increased GH secretion from e20 goose embryonic pituitary cells. 4. A significant increase was observed in the glucocorticoid receptor in GR transcription levels (P < 0.01) with CORT, CORT-BSA, and DEX treatment. Furthermore, the CORT-stimulated GH mRNA expression was completely negated by pre-treatment with RU486. 5. These findings demonstrate that glucocorticoids can stimulate somatotroph differentiation in vitro, as characterised by enhanced GH protein secretion and mRNA expression in cultured geese embryonic pituitary cells. The membrane GR was involved in pituitary somatotroph differentiation induced by glucocorticoids during the embryonic development of geese.